Digital Payment as Everyday Consumption: Consumer Behavior and Generational Differences in QRIS Usage - Anisya Rahmelia; Mimin Aminah; Megawati Simanjuntak (Journal of Child, Family, and Consumer Studies, 2026)
This study aims to describe consumer behavior in the use of Quick Response Code Indonesian Standard (QRIS) as part of everyday digital consumption among Generation X and Generation Z. A quantitative survey approach was employed, involving 175 QRIS users in the Greater Jakarta area. Data were analyzed using descriptive statistics to examine respondent characteristics, usage patterns, and perceptions related to ease of use, loyalty programs, cashless society orientation, perceived risk, trust, satisfaction, and loyalty. The results indicate that QRIS has become embedded in daily consumption activities, with higher usage intensity observed among Generation Z. Overall, respondents report positive perceptions of ease of use and loyalty programs, while perceived risk remains at a moderate level. Differences in behavioral tendencies are observed across generations. Generation X tends to emphasize trust in shaping satisfaction, whereas Generation Z places greater importance on ease of use. Despite these differences, satisfaction is consistently associated with continued usage behavior in both groups. These findings highlight variations in consumer behavior across generations and underscore the importance of consumer education and protection in supporting the effective use of digital payment systems.